INSTITUTIONALIZATION OF OLD BELIEVERS COMUNITIES OF THE VYATKA PROVINCE AFTER THE ISSUANCE OF THE DECREE «ABOUT STRENGTHENING OF THE FIRST PRINCIPLES OF TOLERATION» IN THE YEAR 1905 - Николай Иванович Бронников (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
After the edition in 1905 of the decree «About strengthening of the first principles of toleration» Old Believers acquired the right to freely practise the religion and to officially register communities for the first time. The purpose of this article is to analyze the institutionalization process of Old Believers communities of the Vyatka province after the publication of the decrees of 1905-1906. The research is based on archival documents introduced for scientific use for the first time. The institutionalization process of Old Believers communities has never been a subject of independent research before. The article focuses on the procedure of registration, the statistics of the registered communities, and relationship with officials and representatives of Synod church at the initial stage. Analyzing the research findings, the author shows that there was no unequivocal attitude to the right of legal registration of the communities among Old Believers consents, the greatest activity at registration in the Vyatka province was shown by Old Believers of belokrinitsky hierarchy. The activity of newly established communities was limited in many respects because of imperfection of the legislative base. DOI: http://dx.doi.org/10.12731/2218-7405-2013-2-7